(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article examines the phonetic features of English personal pronouns, including vowel reduction, consonant changes, linking, stress, and dialectal variations. It also discusses phonological adaptation of foreign words, highlighting how unfamiliar sounds are modified to fit English pronunciation, ensuring clarity and natural-sounding speech.